A resource allocation algorithm based on double slots - EIPeng L; IYouming L; ITing L; HOUGuili Z; UCaimei F (Dianxin kexue)
A resource allocation algorithm based on double slots was proposed to minimize the transmitting power in wireless communications.Being aware of the channel difference between the two adjacent slots,the second slot was allocated in advance partial of the data rate conventionally scheduled to the first slot when the corresponding user had perfect channel state.Consequently,most of the required data was loaded by the sub-carriers with fine channel gain and finally less transmitting power was needed.The simulation results indicate that the proposed algorithm can effectively decrease the transmitting power while meeting the users' target rate requirement.